2016
DOI: 10.5194/acp-16-9349-2016
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of OH reactivity above the canopy of an isoprene-dominated forest

Abstract: Abstract. Measurements of OH reactivity, the inverse lifetime of the OH radical, can provide a top–down estimate of the total amount of reactive carbon in an air mass. Using a comprehensive measurement suite, we examine the measured and modeled OH reactivity above an isoprene-dominated forest in the southeast United States during the 2013 Southern Oxidant and Aerosol Study (SOAS) field campaign. Measured and modeled species account for the vast majority of average daytime reactivity (80–95 %) and a smaller por… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(77 citation statements)
references
References 44 publications
11
66
0
Order By: Relevance
“…A detailed analysis of the OH reactivity budget is provided by Kaiser et al (2016). The median diel variation presented here is slightly different from that presented by Kaiser et al because slightly different days are included in the median values.…”
Section: B Measured Oh Reactivitymentioning
confidence: 45%
“…A detailed analysis of the OH reactivity budget is provided by Kaiser et al (2016). The median diel variation presented here is slightly different from that presented by Kaiser et al because slightly different days are included in the median values.…”
Section: B Measured Oh Reactivitymentioning
confidence: 45%
“…During the night, monoterpenes had a larger impact than isoprene due to their known temperature dependency (Kesselmeier and Staudt, 1999). α-Terpinene was the most reactive-to-OH BVOC also during nighttime; see Table 3.…”
Section: Calculated Oh Reactivity and Bvoc Influencementioning
confidence: 99%
“…Here, this is referred to as calculated OH reactivity, and comparisons between the calculated and the measured OH reactivity have showed that discrepancies in various environments exist (Di Carlo et al, 2004;Nölscher et al, 2016). The missing OH reactivity, namely the fraction of OH reactivity not explained by simultaneous measurements of reactive gases, has been associated with unmeasured compounds either primary emitted, secondary generated, or both (e.g., Sinha et al, 2010;Nölscher et al, 2012aNölscher et al, , 2013Edwards et al, 2013;Hansen et al, 2014;Kaiser et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have attempted to identify the missing sink: whilst some authors have attributed the missing reactivity to the presence of primary emissions that escaped detection (Holzinger et al, 2005;Kaiser et al, 2016;Sinha et al, 2010), others have pointed to the reactions of OH with short-lived oxidation intermediates (Hansen et al, 2014;Nakashima et al, 2014), which are notoriously challenging to measure in the field. Other studies still, including that by Nölscher et al (2016) in the Amazon rainforest, attributed the missing reactivity to both unidentified biogenic emissions and photooxidation products.…”
Section: Introductionmentioning
confidence: 99%